ARCA DWARAPALA PADA CANDI-CANDI BUDDHA DI JAWA TENGAH (Paramita: Historical Studies Journal, 2010)
Temple as a product of the culture of Hindu-Buddhist period is the building that describes the concept of cosmogony and a replica of Mount Mahameru the place of the gods. Dwarapala statue is one of the guards in almost Javanese temple. The existence of this statue in the temple (depiction microcosm) has a meaning. Problems which will be solved, namely: (1) where the statue Dwarapala placed in the temple Plaosan and the temple Sewu (2) how is the depiction of Dwarapala statues in the temple Palosan and the temple Sewu? Gana figure that became the object of the study were analyzed with hermeneutical analysis. Hermeneutical analysis of the statue Dwarapala can only be done if the information about these statues is known. From the results of research and discussion can be seen that the meaning of the statue at Buddhist temple Dwarapala not be separated from the concept of cosmogony. Portrayal system was adapted to the function of these statues at the temple. So it can be said that the statues have meaning that Dwarapala is a portrayal of religious situation in the Hindu-Buddhist and the symbol of the world above (heaven). The placement of temple statues Dwarapala complement cosmogony concept representations, thus building meaning of worship into a whole. Keywords:  Dwarapala, temple, hermeneutic   Candi sebagai produk dari budaya masa Hindu-Buddha adalah bangunan yang menggambarkan konsep kosmogoni dan replika Gunung Mahameru tempat para dewa. Patung Dwarapala adalah salah satu penjaga di kuil hampir Jawa. Keberadaan patung ini di candi (mikrokosmos penggambaran) memiliki arti. Masalah yang akan dipecahkan, yaitu: (1) bagaimana patung Dwarapala ditempatkan di candi Plaosan dan candi Sewu (2) bagaimana penggambaran patung Dwarapala di candi Palosan dan candi Sewu? Gana sosok yang menjadi objek penelitian dianalisis dengan analisis hermeneutis. Analisis hermeneutis patung Dwarapala hanya dapat dilakukan jika informasi tentang patung-patung ini dikenal. Dari hasil penelitian dan pembahasan dapat dilihat bahwa arti dari patung pada candi Budha Dwarapala tidak lepas dari konsep kosmogoni. Penggambaran sistem adalah disesuaikan dengan fungsi dari patung-patung di candi. Jadi dapat dikatakan bahwa patung-patung memiliki makna bahwa Dwarapala adalah gambaran situasi agama di Hindu-Buddha dan simbol dunia atas (surga). Penempatan patung Dwarapala candi melengkapi representasi konsep kosmogoni, demikian membangun makna ibadah menjadi keseluruhan.   Kata kunci: Dwarapala, candi, hermeneutik